Sociolinguistic insights into chick lit: Constructing the social class of elegant poverty. (June 2018) - Theodoropoulou, Irene
Abstract: Aiming at suggesting ways whereby the sociolinguistic paradigm can benefit from the analysis of chick lit, this paper explores the ways through which the social class of "elegant poverty" is stylistically constructed in Modern Greek chick lit texts. Although chick lit has been analyzed primarily in terms of gender identity construction, I argue that it can be also seen as a goldmine of styles pertinent to social class due to its rather extravagant but meticulous treatment of social class cultural models and the caustic stylistic representation thereof, both of which aim at increasing the sales of chick lit. More specifically, chick lit offers analytical insights into social classes that are powerful but are traditionally hard to get ethnographic access to, such as elegant poverty in Athens. Relatively recently formed, elegant poverty consists of primarily former wealthy northern Athenian suburbanites who due to the financial recession are characterized by the ownership of estate but absolute lack of cash. Drawing on excerpts from chick lit authored by Pavlina Nasioutzik, it is argued that in chick lit elegant poverty is represented as the amalgam of socioeconomic and cultural models, which are styled through irony, satire and code-switching.